Trypanosoma brucei brucei: In vitro production of metacyclic forms - Hirumi, H.; Hirumi, K.; Moloo, S.K.; Shaw, M.K. (Wiley, 1992)
ABSTRACT An in vitro method has been established to obtain metacyclic form populations of Trypanosoma brucei brucei. Trypanosome populations containing more than 98% of metacyclic forms were obtained from cultures which were: 1) initiated with bloodstream forms in primary cultures in the presence of Microtus montanus embryonic fibroblast‐like cells (feeder cell layers); 2) maintained in glucose‐free Eagle's minimum essential medium supplemented with 10 mM L‐proline, 2 mM L‐glutamine and 20% (v/v) fetal bovine serum at 27° C without medium change for five days; 3) subcultured in the absence of the feeder cell layers but in the presence of Cytodex 3 beads; 4) maintained for an additional nine days with medium changes on days 5, 8 and 11; and 5) harvested on day 14 by means of diethylaminoethyl cellulose column chromatography prior to the appearance of other infective forms. Most of the trypanosomes obtained under these conditions were morphologically similar to metacyclic forms derived from tsetse fly vectors, coated with variable surface glycoprotein and were infective for mice. In the primary cultures procyclic forms, epimastigotes and metacyclic forms appeared by day 8. When the duration of the subculture was prolonged to 17 days or more at 27° C, the metacyclic forms decreased in number while short trypomastigotes, long slender epimastigotes, and long slender trypomastigotes increased in number. These forms in such long‐term cultures also appeared in diethylaminoethyl cellulose‐isolated populations along with metacyclic forms.